Neuronal responses to the scratching and caressing of one's own skin in patients with skin‐picking disorder. Issue 3 (7th December 2017) - Schienle, Anne; Übel, Sonja; Wabnegger, Albert
Abstract: Skin‐picking disorder (SPD) is a common mental disorder. The predominant symptom involves the repeated scratching and picking of one's own skin. This behavior causes severe tissue damage (sores, scars, and infections), often leading to disfigurement. Besides physical injury, SPD is associated with clinically significant distress and impairment in important areas of functioning. The neurobiological mechanisms of SPD are still poorly understood. In this study, 30 SPD patients and 31 control participants (35 women, 26 men) with a mean age of 34 years were instructed to either scratch or gently stroke a small skin area on their arms during functional magnetic resonance imaging. Gender‐specific effects were revealed. In the female sample, SPD patients showed less activation in the middle frontal gyrus (MFG) and primary/secondary somatosensory cortices during caressing relative to scratching than controls. In addition, contrasting caressing with a rest condition revealed reduced activation in the somatosensory cortex (concerned with the decoding and integration of tactile information) and the MFG (attention/cognitive monitoring) in female patients. No differential brain activation was found in the male sample. This symptom provocation study hints at a reduced sensitivity of pleasant touch in women with SPD.